The end of catheter dislodgement? Three facile steps to secure a tunneled central venous catheter - Dayang Anita AA,; Hardip S Gendeh,; Gendeh MK,; Kosai NR,; Mohd Ramzisham Abdul Rahman,; Reynu R, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Central Venous Line (CVL) catheter can easily dislodge. An improvised technique in three easily reproducible steps is described in detail. The placement of the cuff approximately 1cm from the exit wound with the placement of additional sutures at the neck area helps prevent its displacement.